Effect of Different Types of Empathy on Prosocial Behavior: Gratitude as Mediator - Pang, YaLing; Song, Chao; Ma, Chao (Frontiers in Psychology, 2022)
With the development of positive psychology, prosocial behavior has received widespread attention from researchers. Some studies have shown that emotion has a significant influence on individual prosocial behavior, but little research has studied the effect of different types of empathy on college students’ prosocial behaviors. The current study examined the mediating effects of gratitude among the associations between different types of empathy (perspective-taking, fantasy, empathic concern, and personal distress) and prosocial behavior among Chinese college students. For the study, we used the Prosocial Tendency Measurement questionnaire, the Hebrew version of Interpersonal Reactivity Index-C, and The Gratitude Questionnaire that investigated 1,037 participants. The results indicated that gratitude played a mediating role between perspective-taking and prosocial behavior, fantasy and prosocial behavior, empathic concern and prosocial behavior, and personal distress and prosocial behavior, respectively. The current study contributes to a better understanding of the relationship between empathy and prosocial behavior.